IRONIMUS ou l’art d’éclairer par l’image - Valérie de Daran (Recherches Germaniques)
Caricature is often considered the epitome of a distorting image. But this does not take into account the way it derives force from simplification, or its instructive and pedagogical dimension. The cartoons the Austrian caricaturist IRONIMUS (Gustav Peichl) drew for the press over nearly 60 years offer a particularly illuminating survey of political life under the Second Republic. With humour and bonhomie, they represent the main events of Austrian history after 1945 in a sober and distanced analysis.